Sur les « fantasias » marocaines d’Eugène Delacroix - François Pouillon (Revue des Mondes Musulmans et de la Méditerranée)
The notebooks that Eugène Delacroix kept during his travels in Morocco in 1832-1833 are an exceptionally detailed source on displays of horsemanship in the Maghrib. Generally, one traces back to the title of one of his paintings the term fantasia, used to indicate those quite ritualized cavalcades in North Africa. A closer look however reveals that Delacroix never used this term during his stay in Morocco. What he shows in the drawings and paintings that resulted from his sojourn is actually quite different from what one habitually refers to with the term fantasia. The exactitude of his documentation as well as research conducted in Algeria at around the same time on the equestrian practices of the Arabs (especially the comprehensive study on the horses of the Sahara published by General Daumas) indicate that we are dealing with a case of what since Hobsbawm and Ranger has become known as an “invention of tradition”. Because only at about 1850, hence after Emir Abdelkader had put down his arms, we can observe a formalization of these horse plays, as part of an attempt of the colonial powers to charm the local elites. Here we witness the coming about of a sudden historical rupture: the transformation of a warlike practice into folklorized ritual.